PENILAIAN BERBASIS KELAS UNTUK PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA BIOLOGI SMP - Arnetis ' '; Mariani Natalina '; Sri Ayuni ' (Program Studi Pendidikan Biologi, 2014)
The aim of this reasearchwas to develop assessment tools based on class for BiologyScience subject on VIII th grade public Junior High School. This study held on Januaryuntil March 2014. This kind of study was Research and Development. Thisdevelopment is based on ADDIE models which consists of 5 phase, they are Analyze,Design, Development, Implementation and Evaluation. This subject of reasearch wasKI dan KD and main materialis on VIII th grade. This reasearch was analyzed bydescriptive. Validity of assessment tools was determined by average score fromvalidator. 3,6 for written assessment, 3,79 for behavior assessment, 3,86 for workassessment, 3,84 product assessment, 3,91 project assessment, 3,95 for selfassessment, 3,95 for portofolio assessment and all were categorized in very valid.Based on result of reasearch can be concluded that validity result of assessment toolsbased on class for Biology science subject on VIII th grade got very valid category andcould be implemented in learning process.Keywords: Development Reasearch, Assessment Tools Based on Class, BiologyScience Subject